Design of Constant Constant Current Regulator Control System of NBF 1200 Using Programmable Logic Controller at The Airport. Issue 1 (March 2021) - Hartono,; Sudjoko, R I; Hariyadi, S; Kumalawati, D A
Abstract: International Civil Aviation Organization (ICAO) regulated Visual Aids for Navigation stated on Annex 14 Chapter 5 consist of mandatory item which provides important guidance's for piloting the airplane. Presently, the system of visual aids for navigation has been working with the Constant Current Regulator (CCR) which in its development there are various type at CCR used at airport. One type CCR is still widely used at airport today is the CCR NBF 1200 power supply using its control system. Reliability and time respons become problem related those system. Therefore this paper presents an design on CCR NBF 1200 control system simulation to control the brightness level of the lamps which indicating as visual aid for navigation. The result shows brightness level success controlled by PLC remotely based on the power level.